Protecting Child Refugees from Violence: Between Legal Texts and Practical Experiences - Khater, Maya Hasan (Journal of Economic, Administrative and Legal Sciences, 2023)
The number of refugees seeking safe havens is increasing as disputes and armed conflicts worldwide continue to escalate. In the meantime, there is growing concern about children in the refugee community. They are encountering abuses and violations of their fundamental rights, including violence within the family and in schools, care homes, and detention centers. The violence against child refugees is discussed by studying the different types of violence and the implications of these horrendous acts. The legal framework that can be used to protect child refugees from violence is reviewed. Finally, the forms of protection that should be provided to them are identified to find practical solutions that may help prevent their rights from being violated, help them overcome the consequences and effects of seeking asylum, and improve their living conditions.The research concludes that international legal procedures are insufficient to ensure refugee children’s fundamental rights, including the right to the promised security. Therefore, It is necessary to put in place additional mechanisms to protect refugee children from violence and improve existing systems to ensure their well-being.
Keywords: Children's rights; protection of child refugees; violence against child refugees; laws for the protection of child refugees